Analysis of students’ creative thinking skills in ecology: Digital mind maps supporting sustainable development goals - Pinareswati, Arlina Dwi; Rahayu, Yuni Sri; Yuliani, Yuliani (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Creative thinking skills, one of the four components of 21st-century skills, are essential for generating ideas, solving problems, and supporting quality education in line with the Sustainable Development Goals (SDGs), particularly SDG 4 on quality education. However, the 2022 PISA results show that Indonesia is among the 14 countries with the lowest creative thinking skills. To address this issue, innovative learning tools such as digital mind maps are proposed as a solution. Research indicates that digital concept maps, which have been explored as an innovative learning method, can effectively support the development of creative thinking skills. This study aims to assess the creative thinking skills of biology students in an ecology course, with a focus on the topic of biological control. A descriptive quantitative approach was used, involving 21 biology students as participants. A creative thinking skills test covering aspects of fluency, flexibility, originality, and elaboration was administered to the participants. Data were analyzed using a rubric-based scoring system. The results showed that 57.14% of students had moderate creativity, 28.57% were less creative, and 14.28% were creative. The elaboration indicator received the highest score (69.04%), while flexibility received the lowest score (35.71%). Specifically, the results of the fluency and originality tests were also included in the analysis, highlighting students' strengths and weaknesses in various aspects of creative thinking. To enhance creative thinking skills in ecology courses focused on SDGs, the use of digital mind maps is recommended. These concept maps can help organize concepts, stimulate divergent thinking, and encourage students' creativity by providing a clear structure for visualizing and exploring ideas.